Reduced‐intensity conditioning for hematopoietic cell transplantation of chronic granulomatous disease. Issue 2 (30th August 2014) - Oshrine, Benjamin; Morsheimer, Megan; Heimall, Jennifer; Bunin, Nancy
Abstract Hematopoietic cell transplantation (HCT) is the only available curative therapy for chronic granulomatous disease (CGD), but its use is limited by transplant‐related mortality (TRM) in patients who often come to transplant with existing infections or organ dysfunction. Reduction in the intensity of the preparative regimen mitigates these risks, but increases the potential for mixed donor‐recipient chimerism (MC) that may progress to graft loss. Recently a busulfan‐based reduced‐intensity conditioning (RIC) regimen has been described with excellent survival and little MC. We report our experience with a similar RIC regimen at our institution, demonstrating problems with donor chimerism and graft loss. Pediatr Blood Cancer 2015;62:359–361. © 2014 Wiley Periodicals, Inc.